Haematological Alteration in Common Carp (Cyprinus Carpio L) Fish After Exposure for Tow Pesticides Goldate, Alexander and Their Mixture - Salih , Noor Yaseen; Al-Azawi, Ahmed J. Mohammed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The excessive and unwarranted use of pesticides at different stages of crop production can pose a great danger to the aquatic environment, and particularly to ﬁsh. Haematological parameters are indicated to be important for environmental pollution. Blood parameters respond to low doses of pollutants, so hematological changes in common carp fish are used for assessing the effects of contaminants. Toxicological effects of Goldate and Alexander individuals combined as a mixture were observed by monitoring hematological parameters in common carp fish. There were 3 concentration groups (1/10, 1/100, and 1/200) for every pesticide (Goldate, Alexander, and mixture of Goldate and Alexander) exposed to juvenile fish (60–80 gm. in weight) for 6 weeks. During the experimental period, the results showed a significant decrease in the red blood cell mean value (RBC), hemoglobin mean value (Hb), and total protein mean value (TP). While there was a significant increase in the white blood cell mean value (WBC) and albumin mean value (Al) after six weeks of exposure, It was found that these changes increase with increasing pesticide concentrations and exposure periods when they are single. However, these changes are more severe when the fish are exposed to a mixture of pesticides at the same time. This experiment found that these changes increase with increasing pesticide concentrations and exposure periods when they are single, but these changes are more severe when the fish are exposed to a mixture of pesticides at the same time, which is evidence of the synergistic action of these pesticides.